2019
DOI: 10.1620/tjem.247.27
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Associated with Prolonged Hospital Stays for Patients Aged 65 Years or Older with a Vertebral Compression Fracture in a Rural Hospital in Japan

Abstract: Japan is an aging society, and the incidence of diseases related to aging, such as pneumonia, heart failure, vertebral compression fracture (VCF), is increasing. Prolonged hospital stays are becoming a serious social problem, leading to elevated medical expenses. Thus, shortening the period of hospitalization is important. This study aimed to reveal determinants associated with prolonged hospital stays for patients with VCF. Our institution is the primary hospital in a rural area in the Kanto region of Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It should not be ignored that prolonged stay in acute hospitals increases the risk of cognitive impairment and functional dependency (18,19,26), in spite of nursing work in self-care training during the hospital stay and the planning of discharge which occurs with the involvement of the healthcare team. On the one hand, other studies have also demonstrated that prolonged hospital stays are associated with poorer functional status and mobility which in turn will affect the degree of dependency postdischarge (18,19,23,(26)(27)(28). On the other hand, the increase in dependency time seems to be followed by gains in autonomy, even though the correlations were not significant.…”
Section: Discussionmentioning
confidence: 90%
“…It should not be ignored that prolonged stay in acute hospitals increases the risk of cognitive impairment and functional dependency (18,19,26), in spite of nursing work in self-care training during the hospital stay and the planning of discharge which occurs with the involvement of the healthcare team. On the one hand, other studies have also demonstrated that prolonged hospital stays are associated with poorer functional status and mobility which in turn will affect the degree of dependency postdischarge (18,19,23,(26)(27)(28). On the other hand, the increase in dependency time seems to be followed by gains in autonomy, even though the correlations were not significant.…”
Section: Discussionmentioning
confidence: 90%
“…We compared the length of stay in this study with the existing literature on lumbar laminectomy and conservative treatment for vertebral compression fracture. According to a study by Yusuke Watanabe et al, conservative treatment for vertebral compression fractures over 65 years of age results in a longer hospital stay and an average hospital stay of 20.6 ± 4.4 ~ 40.0 ± 11.6 days [ 18 ]. In addition, according to a study by Takeshi Oichi et al, in a study comparing microendoscopic laminectomy and open laminectomy, the average length of hospital stay was 12 and 16 days, respectively.…”
Section: Discussionmentioning
confidence: 99%